Correction: Bioactive peptides derived from milk proteins and their health beneficial potentials: an update. Issue 19 (20th September 2022) - Nagpal, Ravinder; Behare, Pradip; Rana, Rajiv; Kumar, Ashwani; Kumar, Manoj; Arora, Sanu; Marotta, Francesco; Jain, Shalini; Yadav, Hariom
Abstract : Correction for 'Bioactive peptides derived from milk proteins and their health beneficial potentials: an update' by Ravinder Nagpal et al., Food Funct., 2011, 2, 18–27, DOI: ; 10.1039/C0FO00016G .